2012
DOI: 10.1002/14651858.cd004456.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Home visits during pregnancy and after birth for women with an alcohol or drug problem

Abstract: There is insufficient evidence to recommend the routine use of home visits for pregnant or postpartum women with a drug or alcohol problem. Further large, high-quality trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 113 publications
(3 reference statements)
0
22
0
6
Order By: Relevance
“…While it has been recognized that risky maternal drinking can be identified during pediatric visits (Jonas et al, 2012), prevention effort focusing on the period immediately after delivery (usually within a few months) has been found to be of limited effectivenss (Turnbull & Osborn, 2012) or to have only short-term benefits (Fleming, Lund, Wilton, Landry, & Scheets, 2008). Importantly, compared to mother’s drinking during pregnancy, only limited epidemiological data on alcohol use during the postpartem and early parenting periods is available to guide intervention efforts.…”
mentioning
confidence: 99%
“…While it has been recognized that risky maternal drinking can be identified during pediatric visits (Jonas et al, 2012), prevention effort focusing on the period immediately after delivery (usually within a few months) has been found to be of limited effectivenss (Turnbull & Osborn, 2012) or to have only short-term benefits (Fleming, Lund, Wilton, Landry, & Scheets, 2008). Importantly, compared to mother’s drinking during pregnancy, only limited epidemiological data on alcohol use during the postpartem and early parenting periods is available to guide intervention efforts.…”
mentioning
confidence: 99%
“…En artikel af Allen (2007) At der er behov for yderligere forskning påpeges desuden på en raekke sundhedsfaglige områder, blandt andet hjemmebaserede interventioner rettet mod overvaegt blandt børn (Knowlden & Sharma, 2012), ligesom studier vedrørende alkohol eller stofmisbrug af gravide eller kvinder med nyfødte børn (Turnbull & Osborn, 2012) er underbelyst.…”
Section: Betydning Og Effekt Af Hjemmebesøgunclassified
“…A recent systematic review published by the Cochrane Collaboration focused on whether there was potential for improving outcomes for pregnant and post-partum women with an AOD problem via home visits (Turnbull & Osborn, 2012). The authors found that, although individual studies reported a significant reduction in involvement with child protection services, there was insufficient evidence to recommend the routine use of home visits for pregnant or post-partum women with an AOD problem (Turnbull & Osborn, 2012). Similar findings have been reported by Tsantefski and colleagues, who found evidence that home visits after births increased the engagement of women in drug treatment services, but there were insufficient data to indicate if this improved the health of the baby or mother (Tsantefski et al, 2013).…”
Section: Home Visitingmentioning
confidence: 99%
“…• A recent systematic review found that, although individual studies reported a significant reduction in involvement with child protection services, there was insufficient evidence to recommend the routine use of home visits for pregnant or post-partum women with an AOD problem (Turnbull & Osborn, 2012).…”
Section: 2 Key Findings From This Sectionmentioning
confidence: 99%